Pengaruh Kinerja Keuangan Perusahaan terhadap Return Total Saham pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (Universitas Negeri Semarang, 2015)
The empirical purpose of this study was to test the signalling theory empirically through the influence of the current ratio, debt to equity ratio, net profit margin, and total asset turn over partially to word the stock total return of manufacturing companies listed on the IDX in 2012-2013. The variables in this study consist of current ratio (X1), debt to equity ratio (X2), net profit margin (X3), total asset turn over (X4), and stock total return (Y). This research used documentation method as methods of data collection. Multiple linear regression analysis was used as methods of data analysis. The result of this research shows that current ratio variable and net profit margin have insignificant effect on the stock total return. The variables of debt to equity ratio and total asset turn over have significant effect on the stock total return. The result of this research shows that adjusted R2 is 8,3%